In vivo optochemical control of cell contractility at single‐cell resolution. (30th October 2019) - Kong, Deqing; Lv, Zhiyi; Häring, Matthias; Lin, Benjamin; Wolf, Fred; Großhans, Jörg
Abstract: The spatial and temporal dynamics of cell contractility plays a key role in tissue morphogenesis, wound healing, and cancer invasion. Here, we report a simple optochemical method to induce cell contractions in vivo during Drosophila morphogenesis at single‐cell resolution. We employed the photolabile Ca 2+ chelator o ‐nitrophenyl EGTA to induce bursts of intracellular free Ca 2+ by laser photolysis in the epithelial tissue. Ca 2+ bursts appear within seconds and are restricted to individual target cells. Cell contraction reliably followed within a minute, causing an approximately 50% drop in the cross‐sectional area. Increased Ca 2+ levels are reversible, and the target cells further participated in tissue morphogenesis. Depending on Rho kinase (ROCK) activity but not RhoGEF2, cell contractions are paralleled with non‐muscle myosin II accumulation in the apico‐medial cortex, indicating that Ca 2+ bursts trigger non‐muscle myosin II activation. Our approach can be, in principle, adapted to many experimental systems and species, as no specific genetic elements are required. Synopsis: Uncaging EGTA with UV illumination in Drosophila embryos triggers a calcium burst and subsequent myosin‐mediated contraction of the apical surface of the cell. Laser photolysis of photolabile chelator EGTA leads to a reversible calcium burst within seconds. Calcium burst triggers non‐muscle myosin accumulation in the apico‐medial complex, which requires ROCK, but not RhoGEF2. Cells contract within a minute after uncaging, which leads to an approximately 50% drop in cross‐sectional area. Abstract : Uncaging EGTA with UV illumination in Drosophila embryos triggers a calcium burst and subsequent myosin‐mediated contraction of the apical surface of the cell.